2021
DOI: 10.3164/jcbn.20-203
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of yacon roots (<i>Smallanthus sonchifolius</i>) affects gut microbiota and fecal mucin and prevents intestinal inflammation in mice

Abstract: Consumption of yacon (Smallanthus sonchifolius) is associated with beneficial effects such as prevention of metabolic diseases.Yacon root is known to contain various bioactive components including indigestible carbohydrates, but the alteration of intestinal environment after treatment with yacon has not been fully investigated. This study investigated yacon-containing diet effects on the intestinal environment in mice, including microbial composition, short-chain fatty acid levels, and mucus content. After mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…34 It is worth mentioning that SCFAs are rapidly absorbed in the proximal colon and further metabolized in the muscle, kidneys, heart, or brain, and thus, the identification of these compounds in the luminal content can be underestimated. 33 This higher acetate production caused by yacon flour was also observed in other studies in rats with CRC 12,13,23 and mice with induced colitis 35 and CRC. 36,37…”
Section: Discussionsupporting
confidence: 83%
“…34 It is worth mentioning that SCFAs are rapidly absorbed in the proximal colon and further metabolized in the muscle, kidneys, heart, or brain, and thus, the identification of these compounds in the luminal content can be underestimated. 33 This higher acetate production caused by yacon flour was also observed in other studies in rats with CRC 12,13,23 and mice with induced colitis 35 and CRC. 36,37…”
Section: Discussionsupporting
confidence: 83%
“…1 index [4]. Our results showed that 0.8% YREs treatment increased diversity parameters in intestinal microbiota, such as the Observed species, Chao1, ACE, and PD whole tree.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 52%
“…One plant yacon can produce more than 10 kilos of tuberous roots. The yacon root extracts (YREs) exhibit health activities of antioxidant [1], lipid-lowering [2], promoting the growth of bifidogenic bacteria while inhibiting the establishment of pathogenic and putrefactive bacteria [3], and preventing animal from intestinal inflammation and colorectal cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…SCFAs (mainly acetic, propionic and butyric acids) from bacterial fermentation of dietary fiber have been linked to a decrease in inflammation [138,139], as well as improved glucose homeostasis and insulin sensitivity [140]. These compounds improve gut barrier function and inflammatory status through several mechanisms: (1) upregulation of intestinal tight junction proteins [141][142][143]; (2) regulation of tight junction assembly via an activation-dependent mechanism of AMP-activated protein kinase (AMPK) [144][145][146]; (3) increase in Treg cells [141,147]; and (4) increase in anti-inflammatory cytokines and decrease in inflammatory cytokines [147,148].…”
Section: Gut Microbiota-derived Metabolitesmentioning
confidence: 99%